2009
DOI: 10.1123/jce.2.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Student Athlete Wellness: Gender Perspectives

Abstract: A study of wellness aspects among college student athletes at a mid-sized, church-related, undergraduate, liberal arts college in the upper Midwest was conducted during the 2006-2007 school year. The students were asked by their coaches and team leaders to complete the Wellness Evaluation of Lifestyle tool online. The study sample consisted of 273 college athletes, of which 131 were female and 142 were male. Female college athletes had the highest scores in the following areas: exercise, friendship, and love. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The present study showed males were more active than females, engaging in more aerobic activity, strength and endurance exercises (P3, P4, P5), and had more energy due to their physical condition (P7). These findings are consistent with previous studies that also report males to be more physically active (Baldwin et al, 2017;LaFountaine, 2009;Myers & Mobley, 2004). The only question on which females scored higher was listening to their body and seeking advice if something went wrong (P1).…”
Section: E2supporting
confidence: 91%
See 2 more Smart Citations
“…The present study showed males were more active than females, engaging in more aerobic activity, strength and endurance exercises (P3, P4, P5), and had more energy due to their physical condition (P7). These findings are consistent with previous studies that also report males to be more physically active (Baldwin et al, 2017;LaFountaine, 2009;Myers & Mobley, 2004). The only question on which females scored higher was listening to their body and seeking advice if something went wrong (P1).…”
Section: E2supporting
confidence: 91%
“…Previous researchers have examined wellness differences between traditional and non-traditional students (Myers & Mobley, 2004), year of study (LaFountaine et al, 2006), gender (Baldwin et al, 2017;LaFountaine, 2009;Wharf Higgins et al, 2010;Stock et al, 2001), institution type (Baldwin et al, 2017), and college athletics (Beauchemin, 2014;LaFountaine, 2009). Such studies have yielded mixed results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LaFountaine et al (2016) showed that female athletes scored lower than their male athlete counterparts in 14 out of 20 of the wellness categories they assessed. The lowest wellness scores in female athletes were in spirituality, stress management, nutrition, and total wellness, and there were sex differences observed, with females scoring lower than males for a sense of worth, stress management, and leisure (LaFountaine, 2016). These sex differences have also been linked to athletic coping skills (Von Guenthner & Hammermeister, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Female athletes tend to have lower representation in sports science literature, which is concerning because there are differences in physiological and psychological responses to training by sex (Cowley et al, 2021). LaFountaine et al (2016) showed that female athletes scored lower than their male athlete counterparts in 14 out of 20 of the wellness categories they assessed. The lowest wellness scores in female athletes were in spirituality, stress management, nutrition, and total wellness, and there were sex differences observed, with females scoring lower than males for a sense of worth, stress management, and leisure (LaFountaine, 2016).…”
Section: Introductionmentioning
confidence: 99%